2014
DOI: 10.1128/mcb.01704-13
|View full text |Cite|
|
Sign up to set email alerts
|

Rad51-Dependent Aberrant Chromosome Structures at Telomeres and Ribosomal DNA Activate the Spindle Assembly Checkpoint

Abstract: bThe spindle assembly checkpoint (SAC) monitors defects in kinetochore-microtubule attachment or lack of tension at kinetochores and arrests cells at prometaphase. In fission yeast, the double mutant between pot1⌬ and the helicase-dead point mutant of the RecQ helicase Rqh1 gene (rqh1-hd) accumulates Rad51-dependent recombination intermediates at telomeres and enters mitosis with those intermediates. Here, we found that SAC-dependent prometaphase arrest occurred more frequently in pot1⌬ rqh1-hd double mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In fact, severer growth inhibition was observed in the SAC mutants. Short spindles were reported to accumulate in SAC-activated cells, and it was reported that replication intermediates or recombination intermediates can activate SAC ( Nakano et al, 2014 ), resulting in cells with short spindles. SAC was less efficiently activated by overexpression of a PP1bs mutant, consistent with reduced short spindles in this mutant.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, severer growth inhibition was observed in the SAC mutants. Short spindles were reported to accumulate in SAC-activated cells, and it was reported that replication intermediates or recombination intermediates can activate SAC ( Nakano et al, 2014 ), resulting in cells with short spindles. SAC was less efficiently activated by overexpression of a PP1bs mutant, consistent with reduced short spindles in this mutant.…”
Section: Discussionmentioning
confidence: 99%
“…RAD51 is a recombinase that nucleates onto 3′ single DNA strand ends to initiate invasion onto a homologous template, usually provided by the complementary sister chromatid during replication maintaining replication forks and repairs DSBs [41,52,53]. RECQL5 can disrupt RAD51 nucleoprotein filaments, promoting noncrossover products during DNA double-strand break-induced HR and counteracts the inhibitory effect of RAD51 on RAD52-mediated DNA annealing in vitro and in vivo [41].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, SAC activation may be protective against Rif1-induced growth inhibition and cell death. Short spindles were reported to accumulate in SAC activated cells, and it was reported that replication intermediates or recombination-intermediates can activate SAC (Nakano et al, 2014), resulting in cells with short spindles. SAC was less strongly activated by overexpression of a PP1bs mutant, consistent with reduced short spindles in this mutant.…”
Section: Discussionmentioning
confidence: 99%